PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PDAM KOTA KUPANG - Margaretha Dadi Lado; Ronald P C Fanggidae; Tarsisius Timuneno (Journal of Management Small and Medium Enterprises (SMEs), 2019)
The research method is an associative method that uses questionnaires as a data collection tool that is distributed throughout the respondents. The population in the study were all employees. The number of samples taken was 35 respondents. As for analyzing and calculating the overall effect of the independent variable Situational Leadership Style on the dependent variable Employee Productivity that is processed using a computer program SPSS for Window. The results of Simple Linear Regression analysis show that the hypothesis testing proves that the Situational Leadership Style variable has a positive and significant effect on Employee Productivity in PDAM Kota Kupang, it means the higher the Situational Leadership Style, the higher Employee Productivity. Keywords: Situational Leadership Style, Employee Productivity